2016
DOI: 10.2147/nsa.s123681
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial dependence of silver nanoparticles on surface plasmon resonance bands against <em>Escherichia coli</em>

Abstract: This study presents a simple and trouble-free method for determining the antimicrobial properties of silver nanoparticles (AgNPs) based on the surface plasmon resonance (SPR) bands. AgNPs were prepared by chemical reduction method using silver nitrates as a metallic precursor and formaldehyde (HCHO) as a reducing agent and capped by polyethylene glycol. Effects of several processing variables on the size and shape of AgNPs were monitored using an ultraviolet–visible spectrophotometer based on their SPR bands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 45 publications
1
28
0
2
Order By: Relevance
“…In addition, their superior properties were used for the determination of the critical micelle concentration of cationic surfactants . Also, their antimicrobial capability was found to depend on the surface plasmon resonances . Moreover, an AgNP‐based sensor provides a pathway to ultrasensitive biodetection experiments with extremely simple, small, light, robust, and low‐cost instrumentation .…”
Section: Properties Of Silver Nanoparticlessupporting
confidence: 64%
“…In addition, their superior properties were used for the determination of the critical micelle concentration of cationic surfactants . Also, their antimicrobial capability was found to depend on the surface plasmon resonances . Moreover, an AgNP‐based sensor provides a pathway to ultrasensitive biodetection experiments with extremely simple, small, light, robust, and low‐cost instrumentation .…”
Section: Properties Of Silver Nanoparticlessupporting
confidence: 64%
“…Through SPR bands, was possible to confirm that nanoparticles were formed at the different pH (figure 1). The wavelength peaks were between 415 and 440 nm, characterizing particles with average diameter between 35 and 80 nm, as described by Solomon et al [19]. Moreover, the size distributions of the nanoparticles were studied as a function of different pH and its formation was confirmed with the yellow/brownish color.…”
Section: Uv-vis Spectroscopymentioning
confidence: 72%
“…UV-vis spectroscopy is the method widely used to the characterization of silver nanoparticles, and through this analysis is possible to confirm the synthesis of nanoparticles, with the correlation between the peak observed at a given wavelength and the average nanoparticle diameter (table 2). In addition, through the width of the SPR bands, it is possible to verify the dispersion of nanoparticles [19]. Through SPR bands, was possible to confirm that nanoparticles were formed at the different pH (figure 1).…”
Section: Uv-vis Spectroscopymentioning
confidence: 91%
“…The [21,22]. A broader peak at 450-480 nm and 420-430 nm were reported for chemical and biological synthesis of AgNPs respectively [15,20]. The different UV-vis spectra for growing the bacteria on different concentrations of AgNO 3 were shown in a previous study [1].…”
Section: Toxicity Effect Of Biologically Produced Agnps On E Coli Anmentioning
confidence: 95%
“…McShan et al [15] showed one of the toxicity mechanism which is oxidative stress via reactive oxygen species (ROS) generation, damaging cell membrane and other cell components including DNA, depleting antioxidant molecules (e.g., glutathione), disabling proteins, lowering reductase activity, reducing protein expression and depressing the activity of some membranous enzymes. Another study showed that apoptosis of E. coli increased with the increase in AgNPs concentrations (5 or 10 μg/ml) of 5-10 nm size [13] in addition to the interaction of both silver ionic and AgNPs form with sulfurcontaining macromolecules such as proteins, due to the strong affinity of silver for sulfur [15].…”
Section: Introductionmentioning
confidence: 99%